Tugas Berbasis Proyek Untuk Pencapaian Keterampilan Kolaborasi Dan Komunikasi Di Tingkat Perguruan Tinggi - Engliana, Engliana; Ekarina, Ekarina (Cetta: Jurnal Ilmu Pendidikan, 2024)
This research presents practical and innovative practices in the form of proposed class activities for college-level learning designs (assignments) focusing on collaboration and communication skills through behaviorist learning theory and social learning theory approaches. These two skills emphasize 21st-century competencies with the integration of Education 5.0. and Social Emotional Learning concepts. So, the main objectives of this paper are (a) how students are prepared to understand concepts and practice collaboration and communication skills and (b) form project assignments suitable for collaboration skills and active thinking from the themes understood. A qualitative method utilizes a literature review approach to investigate the process of developing project-based learning plans for classroom activities. Analysis of the discussion focuses on collaboration and communication skills through behaviorist learning theory and social learning theory approaches. The results of the learning design and class assignments show that collaboration and communication skills can be achieved through repeated continuous project assignments and feedback from colleagues in the class and lecturers. To hone collaboration and communication skills, repetitive project assignments, reinforcement, and rewards should be considered when designing special assignments for early semester students to equip them with people skills in an increasingly connected and rapidly evolving global landscape. Apart from that, this approach from the two theories in project assignments makes students accustomed to cooperation, time management, and communication. In conclusion, students need to convey ideas in oral and written form. Higher education needs to provide opportunities for students to participate in collaborative projects, group discussions, and presentations and be strengthened using digital communication technologies.